(untitled) (Journal of Engineering, 2007)
The main title of the study is “THE GEOMETRICAL FORM IN MUSICAL HALL THROUGH THE CLASSICAL AND MODERN AGES” We live in a world full of sounds performed by human and different creatures which surround us from every direction, it’s not strange to know that acoustics has gone a long way through human experience because its related to many sides as mathematics and physics with accordance to architecture side, This side is related to the nature of space and its speech or music variation, each use has certain determiners that affect the efficiency of acoustic performance. Musical halls have a main characteristic on the design and performing level through different periods. The architectural and acoustical literature’s have dealt with this type of hearing space in deter minding the geometrical role in music halls design have never been studied with connection with music properties and in comprehensive way, and for this reason it was specified as research problem (The role of the shape, dimension, rates size and relation) So there are many acoustic features in musical sound affected by acoustic space geometry (shape, dimension, rates, size, and relation) Thus the researches aim the following: Finding the geometrical evolution and induct geometric efficient through: Comparative analysis for musical spaces and halls through the classical and modern ages to discover the nature of their geometric form in a descriptive, mathematical and graphical ways and show its role in the efficiency of acoustic performance.